2003
DOI: 10.1046/j.1524-475x.2003.11306.x
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a new liquid occlusive dressing for excisional wounds

Abstract: We evaluated a novel octylcyanoacrylate-based liquid occlusive dressing for partial-thickness wounds. One hundred and fifteen standardized wounds were created with an electric dermatome set at a depth of 600 micro on the flanks of three pigs and randomly treated with liquid occlusive dressing, a hydrocolloid dressing, or gauze. In one pig, wounds were swabbed with Staphylococcus aureus. Biopsies were taken after 4, 5, 6, and 21 days. Hemostasis was obtained in all wounds treated with the liquid occlusive. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
16
1

Year Published

2005
2005
2012
2012

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(17 citation statements)
references
References 38 publications
(41 reference statements)
0
16
1
Order By: Relevance
“…As such, frequent dressing changes would no longer be an advantage when reapplication of the OCA was required. The results of our study are in contrast with those involving superficial abrasions in humans 16 and animals, 14,15 and noncontaminated 10,12 and contaminated 11 burns in a porcine model. The failure of the OCA adhesive to perform consistently in human burns is probably explained by the presence of a large amount of weeping and exudates typical of superficial, partialthickness (second-degree) burns.…”
Section: Discussioncontrasting
confidence: 94%
See 1 more Smart Citation
“…As such, frequent dressing changes would no longer be an advantage when reapplication of the OCA was required. The results of our study are in contrast with those involving superficial abrasions in humans 16 and animals, 14,15 and noncontaminated 10,12 and contaminated 11 burns in a porcine model. The failure of the OCA adhesive to perform consistently in human burns is probably explained by the presence of a large amount of weeping and exudates typical of superficial, partialthickness (second-degree) burns.…”
Section: Discussioncontrasting
confidence: 94%
“…13 Singer et al reported similar results after treating deep, partial-thickness excisional wounds with OCA in a porcine model. 14 Davis et al found that small, superficial, partialthickness porcine wounds treated with a slightly different and weaker version of a liquid OCA healed faster than those treated with a hydrocolloid dressing. 15 An OCA-based liquid bandage has also been shown to reduce pain and bleeding while resulting in healing similar to that with standard bandages in patients with minor cuts and scrapes.…”
mentioning
confidence: 99%
“…They also found that only 2-octyl cyanoacrylate provided complete hemostasis, reduced scab formation, and did not induce an irritant response or infection. Singer et al [25] evaluated a stronger 2-octyl cyanoacrylate formulation for the treatment of larger and deeper (0.6 mm) excisional wounds in swine. They found that the rates of re-epithelialization of 2-octyl cyanoacrylate treated wounds were similar to wounds treated with hydrocolloid and better than those treated with dry gauze.…”
Section: Discussionmentioning
confidence: 99%
“…Middelkoop et al developed an excisional model for testing dermal and epidermal substitutes and for scald and contact burns [2] which favored a burn size of approximately 50 cm 2 . Several porcine burn models, detailed descriptions of burn depth and scar assessments, and dressing application methods have been published by Singer et al [3-5,20,21]. Mittermayr et al [22] developed a pig model of excision and grafting with non-meshed skin autograft and performed wound healing measurements for 2 weeks.…”
Section: Discussionmentioning
confidence: 99%